Anaesthetic management of a case of giant cerebral aneurysm with persistent hypoglossal artery - Bharamagoudar, Prakash C.; Monteiro, Joseph N.; Chelani, Ratan R.; Goraksha, Shwetal U. (Journal of Neuroanaesthesiology and Critical Care, 2016)
The persistent hypoglossal artery is a rare carotid basilar anastomosis associated with hypoplastic or absent vertebral arteries. We report a case of clipping of a 2.5 cm size giant aneurysm just distal to the persistent hypoglossal branch, using intra-arterial balloon occlusion and adenosine induced near flow arrest method. It was an anaesthetic challenge to maintain haemodynamic and homeostatic equilibrium throughout the procedure.
Keywords: Adenosine; giant aneurysm; intra-arterial balloon occlusion; persistent hypoglossal artery